Accident Detection for Automobiles Switch and Buzzer (International Journal of Engineering and Computer Science, 2018)
The objective of this paper is to detect the accident of an automobile. Where the module is integrated inside the automobile to detect the accident and reduce the major injuries and loose of life. The accelerometer sensor detects the accident. If an automobile is met with an accident then, sensor will be activated and the location of the accident will be sent to emergency stations.